2021
DOI: 10.3389/fmars.2021.738877
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Marine Fungi in Plastic Degradation – A Review

Abstract: Plastic debris has been accumulating in the marine realm since the start of plastic mass production in the 1950s. Due to the adverse effects on ocean life, the fate of plastics in the marine environment is an increasingly important environmental issue. Microbial degradation, in addition to weathering, has been identified as a potentially relevant breakdown route for marine plastic debris. Although many studies have focused on microbial colonization and the potential role of microorganisms in breaking down mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 191 publications
2
52
0
3
Order By: Relevance
“…Plastics accumulating in the marine environment are an increasingly important environmental issue [ 34 ]. Most of the plastic waste is accumulated in the sea, and there will be more plastics in the sea than fish by 2050.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastics accumulating in the marine environment are an increasingly important environmental issue [ 34 ]. Most of the plastic waste is accumulated in the sea, and there will be more plastics in the sea than fish by 2050.…”
Section: Discussionmentioning
confidence: 99%
“…Iram et al [ 33 ] reviewed some of the most common strategies for the degradation of various types of polymers, along with a list of potential microbes capable of feeding on them. The role of marine fungi was also recently reviewed by Zeghal et al [ 34 ]. Microbial degradation of plastics was reviewed by Kale et al [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As fungi are known to produce a variety of enzymes that have the potential to break down the chemical bonds of plastic polymers, they might have a role in the degradation of marine plastics [ 112 ]. Seminal works on plastic deterioration by marine fungi have suggested that polyurethanes are more susceptible to fungal attacks [ 113 ].…”
Section: Ecological Roles Of Mycoplanktonmentioning
confidence: 99%
“…Besides being a source of bioactive compounds, marine fungi are also recognized for their metabolic capacities for bioremediation. This capacity aids, for instance, in the degradation of recalcitrant cell wall compounds (marine fungi express catalases, laccases, peroxidases) and environmental contaminants (e.g., toxic pollutants and microplastics) [11].…”
Section: Introductionmentioning
confidence: 99%